2010
DOI: 10.3310/hta14220
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of cognitive behaviour therapy and motivational interviewing for people with Type 1 diabetes mellitus with persistent sub-optimal glycaemic control: A Diabetes and Psychological Therapies (ADaPT) study.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(98 citation statements)
references
References 302 publications
2
92
0
4
Order By: Relevance
“… Recommendation 19 : CBT should be recommended either alone or in combination with other strategies to diabetes patients with co-morbid psychiatric disorders or to improve glycemic control and emotional well-being[7879] (Grade A; EL 1). Recommendation 20 : Healthcare professionals should receive formal training in CBT[28] (Grade A; EL 1). Recommendation 21 : A simple method that can be followed in the Indian context is the Karnal Model for counseling[80] (Grade A; EL 1). Recommendation 22 : Healthcare professionals should have at least eight sessions with the patient during the therapy[76] (Grade C; EL 3). Karnal model[3180] : The Karnal model relies on the cognitive behavioral therapy approach, which follows the “antecedents’ lead to behavior’ leads to consequences” (ABC) framework which will be effective only if a complete history of the patient is considered. The model represents an easy, simple and acceptable method of counseling applicable to various psychological disorders and can be used in all health care situations, including similar resource-challenged settings with social constraints.…”
Section: Psychological Assessment and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“… Recommendation 19 : CBT should be recommended either alone or in combination with other strategies to diabetes patients with co-morbid psychiatric disorders or to improve glycemic control and emotional well-being[7879] (Grade A; EL 1). Recommendation 20 : Healthcare professionals should receive formal training in CBT[28] (Grade A; EL 1). Recommendation 21 : A simple method that can be followed in the Indian context is the Karnal Model for counseling[80] (Grade A; EL 1). Recommendation 22 : Healthcare professionals should have at least eight sessions with the patient during the therapy[76] (Grade C; EL 3). Karnal model[3180] : The Karnal model relies on the cognitive behavioral therapy approach, which follows the “antecedents’ lead to behavior’ leads to consequences” (ABC) framework which will be effective only if a complete history of the patient is considered. The model represents an easy, simple and acceptable method of counseling applicable to various psychological disorders and can be used in all health care situations, including similar resource-challenged settings with social constraints.…”
Section: Psychological Assessment and Managementmentioning
confidence: 99%
“…Recommendation 19 : CBT should be recommended either alone or in combination with other strategies to diabetes patients with co-morbid psychiatric disorders or to improve glycemic control and emotional well-being[7879] (Grade A; EL 1).…”
Section: Psychological Assessment and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 19 studies from the USA, six from the UK, three from Germany, two from Ireland, and one from each of Australia, Bulgaria, Canada, Denmark, India, Italy and the Netherlands (Tables and ; further details in Appendix S2). The studies were classified according to the type of intervention assessed: education programmes ( n = 22); telemedicine ( n = 11); community pharmacist‐based interventions ( n = 3); and behavioural change interventions ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to improving psychological well-being, psychological interventions have been shown to signifi cantly improve glycaemic control in patients, with a mean reduction in glycated haemoglobin (HbA1c) of 0.5% associated with 12 sessions of a face-to-face programme involving motivational interviewing plus CBT. 19 A recent randomised controlled trial of adherence-focused CBT has demonstrated similar improvements. 20 …”
Section: Psychological Treatments Improve Outcomesmentioning
confidence: 91%